Anatomy in the animal kingdom (Nature Portfolio, 2021)
Abstract Examining the anatomy of an organism opens up a whole world of exploration into the function of its body, its evolution, and how it interacts with the biotic and abiotic elements in its environment. On the cusp of new advances in technology that have furthered this exploration, the editors at Communications Biology have gathered a Collection of our exciting research in organismal anatomy to highlight the possibilities of this field yet to come.